A byte-size multi-variable-length-code based string matching algorithm for Alpha image coding - Liping ZHAO; Tao LIN; Kailun ZHOU; Hua PENG; Keli HU (Dianxin kexue)
According to the characteristics of Alpha image and the statistical characteristics of coding parameters of string matching algorithm,an Alpha image coding algorithm based on byte-size multi-variable long-length string matching was proposed.The algorithm firstly used a byte-type multi-variable long-code scheme for joint optimization coding of multiple string matching coding parameters,the offset parameter was then encoded using a segmentation mapping scheme with proximity offset prioritization.Finally,the matching string length parameter was matched with a segmentation coding scheme.The experimental results show that compared with LZ4HC,zlib,PNG and HEVC (x265),the proposed algorithm has the advantages of ultra-low complexity and high coding efficiency.